LAMP2A-dependent chaperone-mediated autophagy enhances oxidative stress resistance in gastric cancer cells through selective degradation of accumulated oxidized DJ-1 - Shuangshuang Le; Tongtong Guo; Meng Yang; Tianjuan Tang; Zhijie Liu; Yang Zheng; Maogui Pang (PLoS ONE, 2026)
Chaperone-mediated autophagy (CMA) promotes cancer cell survival by selectively removing oxidatively damaged proteins, yet its precise molecular mechanisms and role in redox adaptation remain incompletely understood. This study aimed to elucidate the function of CMA in regulating oxidative stress resistance in gastric cancer (GC) cells, focusing on the LAMP2A–DJ-1 regulatory axis. LAMP2A expression was assessed in GC tissues and cell lines via immunohistochemistry, qPCR, and western blot. Oxidative stress models were established using hydrogen peroxide (H₂O₂). Genetic manipulation of LAMP2A was performed to evaluate its impact on cell proliferation, apoptosis, and CMA substrate recognition. Protein interactions were examined by co-immunoprecipitation and immunofluorescence. We found that LAMP2A was upregulated in GC and further induced by oxidative stress. Knockdown of LAMP2A impaired CMA activity, sensitizing GC cells to H₂O₂-induced apoptosis. DJ-1, an antioxidant protein, was identified as a CMA substrate containing a conserved KFERQ-like motif. Oxidative stress enhanced DJ-1–LAMP2A interaction and promoted their lysosomal colocalization. LAMP2A deficiency led to accumulation of hyperoxidized DJ-1, concomitant with upregulation of pro-apoptotic BAX and downregulation of anti-apoptotic Bcl-2. We identify hyperoxidized DJ-1 as a novel CMA substrate and demonstrate that LAMP2A-dependent clearance of oxidized DJ-1 constitutes a key adaptive mechanism that maintains redox homeostasis and promotes survival in gastric cancer cells under oxidative stress.